INOVASI PELAYANAN PUBLIK MELALUI KALIMASADA (KAWASAN LINGKUNGAN SADAR ADMINISTRASI KEPENDUDUKAN) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SURABAYA - Alifianka Prila Permata; Agus Widiyarta (STIE Trisna Negara OKU Timur, 2022)
To achieve the quality of public services, the government needs to issue innovations in the field of public services to facilitate people's lives. The Department of Population and Civil Registration of the City of Surabaya as a government agency wants to create people who know about population administration by organizing the KALIMASADA program through the KALIMASADA pilot RT. Therefore, this study discusses the innovation of the KALIMASADA Program in improving the quality of service in the city of Surabaya. The object of research is the Department of Population and Civil Registration of the City of Surabaya. The purpose of this study was to identify KALIMASADA program innovations in increasing population administration awareness. The research method used is descriptive with a qualitative approach using interview techniques with previously prepared questions. And analysis of literature study based on theory from previous studies. The results of this study indicate that the KALIMASADA program is running well because it has cut bureaucracy by simplifying requirements and procedures. However, it should be noted that the facilities and infrastructure do not meet public service standards, so that it becomes an obstacle.